Optimasi Starter dalam Memproduksi Inulinase dan Identifikasi Khamir Inulinolitik BAN - 1 dari Umbi Dahlia (Dahlia variabilis Willd) - Wijanarka Wijanarka; Endang Kusdiyantini; Hermin Hermin (Fakultas Biologi | Universitas Jenderal Soedirman, 2010)
Inulinolitic yeast isolated from dahlia tuber (Dahlia variabilis Willd) of Bandungan-Ambarawa, was found to produce inulinase enzyme (E.C.3.2.1.7). Under tested fermentation condition, BAN-1 inulinase isolate showed enzymatic activity in dose dependent manner to the starter concentration. A maximum enzymatic activity of 0.582 IU was produced by adding starter concentration 10%. Based on morphological, physiological and biochamichal evaluation it was indentified that the BAN-1 isolate is Pichia sp.